2021
DOI: 10.1186/s42834-021-00087-7
|View full text |Cite
|
Sign up to set email alerts
|

Performance of horizontal flow constructed wetland for secondary treatment of domestic wastewater in a remote tribal area of Central India

Abstract: The purification of the primary treated domestic sewage was performed in the present study through the horizontal sub-surface flow constructed wetland (CW) of 10 × 3.5 m dimension. The study was performed using three setups of CW 1 (Unplanted CW), CW 2 (CW planted with macrophyte Typha latifolia), and CW 3 (CW planted with two species of macrophyte T. latifolia and Commelina benghalensis). The purification experiments were performed by converting one type of CW into the other form sequentially, i.e., CW 1 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…53 An increase in DO facilitates the oxidation process within the wetland system. 54 In the planted wetland, the effect of the root zone might have enhanced the concentration of DO. In addition to this, increase DO level in the effluent of the constructed wetlands might be related to the removal of organic substances through the various means.…”
Section: Resultsmentioning
confidence: 99%
“…53 An increase in DO facilitates the oxidation process within the wetland system. 54 In the planted wetland, the effect of the root zone might have enhanced the concentration of DO. In addition to this, increase DO level in the effluent of the constructed wetlands might be related to the removal of organic substances through the various means.…”
Section: Resultsmentioning
confidence: 99%
“…where area (a) was the forested landscape and water bodies (in ha) at the earliest reported year in the paper (1990), while area (b) referred to the final year (2018). Removal efficiency or load reduction [41,97] for each of the water quality parameters measured per year was calculated using the following Formula (2):…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that at hydraulic retention time of 5.9 days, the most probable mechanism for this removal is microbial decomposition in the plant roots as well as adsorbtion/absorption. To treat a primary treated sewage, Shukla et al [61] study three HF CWs (35 m 2 each) filled sequentially and supplied with gravel media. CW 1 (unplanted), CW 2 (planted with Typha latifolia) and CW 3 (planted with Typha latifolia and Commelina benghalensis).…”
Section: Horizontal Sub-surface Flow Constructed Wetlandsmentioning
confidence: 99%